Towards “Kalimatun Sawa”: A dialogue between Islam and Christianity on the universal good - Ardiansyah Ardiansyah; Yogi Prihantoro (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
Relations between Islam and Christianity experienced debate and conflict, and this even led to violence. Even if it is realized that the two religions teach kindness to others. Debates and conflicts between the two religions can be reduced by means of kalimatun sawa, seeking a common meeting point between the two religions. Thus, this article aims to explain how the kalimatun sawa is based on the relationship between Islam and Christianity. The research method used is literature review with a comparative theology approach of religions. The results of the research are that Islamic and Christian dialogue must be based on building a high sense of tolerance and carrying out social activities to spread goodness in society.